Evaluasi Drug Related Problems (DRPs) Pada Pasien Congestive Heart Failure (CHF) Di Instalasi Rawat Inap RSUD Dr. Soedirman Tahun 2022 - Dewi, Rahmatia Candra; Ainni, Ayu Nissa; Miyarso, Chondrosuro; Widiatuti, Tri Cahyani (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Congestive Heart Failure (CHF) is a chronic condition in which the heart is unable to pump blood as it should. Comorbidities and the use of polypharmacy drugs in the treatment of Congestive Heart Failure (CHF) are risk factors that trigger Drug Related Problems (DRPs). The purpose of this study was to identify and evaluate Drug Related Problems (DRPs) in Congestive Heart Failure (CHF) patients at the inpatient ward of RSUD Dr. Soedirman Kebumen in 2022. This research is a descriptive non-experimental study with a retrospective method. DRPs analysis was carried out based on the type of DRPs found using the Pharmaceutical Care Network Europe (PCNE) V9.0 reference and then compared with the 2020 guidelines for the management of heart failure. Data obtained from 110 patients showed there were 49 DRP events which included 26 untreated indications (53.06%), 16 incidents of overdose (32.65%), 4 incidents of drugs without indications (8.16%), 3 incidents of therapeutic duplication (6.12%) and 0 incidents of underdose (0%). Based on the PCNE V9.0 classification, the most common cause of DRPs at RSUD Dr. Soedirman Kebumen in 2022 was untreated indications. As a recommendation, it is necessary to evaluate DRPs in CHF patients by observing potential side effects prospectively.